Processamento auditivo (central): o discurso de um grupo de fonoaudiólogos - Rocha, Camila de Almeida (2008)
The (central) auditory processing is the efficiency and effectiveness with which the central auditory nervous system processes the sounds, from its reception to its interpretation. Perceptual, cognitive and linguistic mechanisms have an influence on recognizing, decoding and interpreting the information heard. Because it consists of a cerebral activity, it is able to link the acoustic signal to its linguistic meaning. This highly complex process of neural pathways can be affected by several conditions inherent to its development and suffered illnesses. Therefore, the assessment of (central) auditory processing and all the segments through which it evolves represent a challenge to the professional involved. The Neuroscience contributes to the area of (central) auditory processing, once it attempts to comprehend the nervous system and its development. Given the necessity of definition and guidance on the practical care of human communication disorders, which includes the (central) auditory processing disorder (C)APD, incorporated to this new paradigm of Neurosciences, it is considered relevant to investigate the concepts and the context of this expanding field. Objective: To prepare the speech of the collective subject starting from the central ideas presented by a group of speech-language pathologist/audiologist. Method: this research counts with the participation of eight speech-language pathologist/audiologists who work in the field of evaluation and/or therapy of (central) auditory processing. They have been interviewed about six central themes: auditory processing (theme 1), (central) auditory processing disorder (theme 2), hearing and language (theme 3), perception (theme 4), set of tests and standardization (theme 5) and differential diagnosis (theme 6). The qualitative method has been used based on the Collective Subject Speech of Lefèvre. The interviews have been recorded and then transcribed. Result: After the construction of speech from key expressions of each subject, central ideas have been identified. In relation to theme 1: "processes: take place from the ear to the brain", "what we do with what we hear" and "expanding area". In relation to theme 2: "nomenclature", "difficulty in one or more of the hearing skills", "related or not to other disorders", "impacts X compensation . In relation to theme 3: "to see the subject as a whole", "hearing: sensation and language: symbolism , "hearing: the preferable way to the oral language", "Hearing: a significant way to the language development" and "deaf: damage in the development of oral language". In relation to theme 4: "the entrance of any sensory information" and "internal representation of feelings. In relation to theme 5: "selection of tests and procedures", "established rules" and "standardization in Brazil". In relation to theme 6: "to differentiate diseases with the same symptoms (comorbidities) and "multidisciplinary team". Conclusion: the assembling of the six proposed themes have been organized in a single speech as if only one speech-language pathologist/audiologist were talking about (central) auditory processing and its implications